STEPPING IN THE RIGHT DIRECTION TOWARDS FULLY REALISING THE CONSTITUTIONAL PROMISE OF SECTION 29(1)(A) OF THE CONSTITUTION: Federation of Governing Bodies for South African Schools (FEDSAS) v Member of the Executive Council for Education, Gauteng and Another 2016 (4) SA 546 (CC) (The Pretoria Student Law Review, 2021)
This note discusses the critical facts controlling the issues of the FEDSAS case, the court’s holding and reasoning thereof, prior litigation regarding admissions to public schools and how the court’s decision actualises the right envisaged in section 29(1)(a).
Keywords: FEDSAS case; admissions to public schools